2020
DOI: 10.1039/c9cp05938e
|View full text |Cite
|
Sign up to set email alerts
|

Thermal transport in amorphous small organic materials: a mechanistic study

Abstract: Heat carriers in amorphous organic materials can be categorized into low frequency propagon and high frequency diffuson, which can partly convert to each other with the variation of pressure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…6, the thermal transport is dominated by <2 THz phonons, and the contributions of <2 THz phonons to the thermal conductivity are 58% for DNTT, 94% for Ph-DNTT, and 66% for C 10 -DNTT, which is consistent with the small-molecule/2D organic semiconductors. 41,48…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…6, the thermal transport is dominated by <2 THz phonons, and the contributions of <2 THz phonons to the thermal conductivity are 58% for DNTT, 94% for Ph-DNTT, and 66% for C 10 -DNTT, which is consistent with the small-molecule/2D organic semiconductors. 41,48…”
Section: Resultsmentioning
confidence: 99%
“…4 (a-f ) reveal differences between the side chains and the main chains, which arise from the discrepancies of composition and orientation. In organic materials, low-frequency phonons are the primary contributors to thermal transport, 31,41 so the vibrational coupling in the 0 ∼ 10 THz range is of significance. The calculated values of S of Ph-DNTT and C 10 -DNTT are as follows: 0.110 and 0.104 for the along-chain, 0.101 and 0.098 for the inter-chain, 0.103 and 0.105 for the cross-chain.…”
Section: Vibration Coupling Investigationmentioning
confidence: 99%
See 1 more Smart Citation
“…So, theoretical and computer simulation-based methods in this regard have been applied rapidly, particularly after recent notable advances in computational tools. Molecular Dynamics (MD) simulation and density functional theory (DFT) are methods in this regard that have been successfully implemented in modeling various systems including vibration behavior [12][13][14][15][16][17] mechanical and thermal properties [18][19][20][21][22][23][24][25][26][27] and electronic properties. [28][29][30][31] DFT is a time-consuming method providing the most accurate results, while MD simulation is less time-consuming but its results firmly rely on the interatomic potential functions.…”
Section: Introductionmentioning
confidence: 99%
“…An et al investigated the effects of water content and cross-linking on the thermo-mechanical property of polyacrylamide hydrogels [28]. Zhou and Volz et al investigated the impacts of pressure on thermal conductivity of two small organic materials [29]. Luo et al demonstrated that strong chain backbone [30,31] and large spatial extension [32,33] play a pivotal role in thermal transport of polymers.…”
Section: Introductionmentioning
confidence: 99%